2020
DOI: 10.1097/bpo.0000000000001672
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Lower Limb Lengthening Using the PRECICE Nail: Our Experience With 50 Cases

Abstract: Background: Limb lengthening using intramedullary externally controlled motorized devices is becoming increasingly popular. There is limited literature regarding their use in the pediatric and adolescent population. This study reviews outcomes on 50 consecutive cases of intramedullary lower limb lengthening surgery in this population. Methods: A retrospective review of all pediatric and adolescent patients treated in our institution by intramedullary le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
39
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 25 publications
6
39
1
Order By: Relevance
“…Studies by Szymczuk et al [ 30 ] and Hammouda et al [ 32 ] compared the PRECICE intramedullary nailing with external fixation, but in our analysis, we only took into account the PRECICE nailing results. In studies by Nasto et al [ 27 ] and Iliadis et al [ 29 ], both retrograde and antegrade approaches were used, and some tibia nailing was included. Other studies preferred the antegrade approach to the femur.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies by Szymczuk et al [ 30 ] and Hammouda et al [ 32 ] compared the PRECICE intramedullary nailing with external fixation, but in our analysis, we only took into account the PRECICE nailing results. In studies by Nasto et al [ 27 ] and Iliadis et al [ 29 ], both retrograde and antegrade approaches were used, and some tibia nailing was included. Other studies preferred the antegrade approach to the femur.…”
Section: Resultsmentioning
confidence: 99%
“…The average lengthening achieved reported by Nasto et al [ 27 ] was 4.4 ± 1.2, with a nail accuracy and reliability of 91% and 88% respectively. Iliadis et al [ 29 ] reported a nail accuracy of 96% and a nail reliability of 98%, due to a single case where a nail was implanted without lengthening because of the patient’s mental health issues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unrelated to these adverse events, the MHRA also raised concerns about a potentially "inappropriate use in children and adolescents" (British Orthopaedic Association 2021). The MHRA acknowledges a widespread use of PRECICE devices in this age group, but highlights that the nails have not been validated for use in these patient groups (Frommer et al 2018, Nasto et al 2020, Iobst 2020, Iliadis et al 2021, Vogt et al 2021. In our study, 10/27 patients were younger than 18 years old with the youngest patient being 11 years of age.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Lee et al (2017) describe broken bushings of PRECICE nails, but no corrosion. However, based on these studies and the body of evidence, clinical application of the titanium PRECICE nail is relatively safe (Alrabai et al 2017, Calder et al 2019, Horn et al 2019, Hammouda et al 2020, Morrison et al 2020, Nasto et al 2020, Frost et al 2021, Iliadis et al 2021b.…”
Section: Discussionmentioning
confidence: 99%